X-Rotor, an Innovative Offshore Wind Turbine to Reduce Cost of Energy - William E. Leithead; Abbas Mehrad Kazemi Amiri; Arthur Camciuc; Laurence Morgan; James Carroll; Julian Feuchtwang (Energies)
The cost of energy generated by large-scale vertical-axis wind turbines faces great challenges for it to be competitive with conventional horizontal-axis wind turbines for offshore deployment. To become competitive, significant reductions in capital cost and operational costs would be competitive. A novel vertical-axis wind turbine that aims to meet these requirements is proposed: the X-rotor wind turbine. An early-stage feasibility study of exemplary two- and three-bladed 5 MW turbines is reported. The cost savings arising from two aspects of the concept that have the greatest impact, namely the power take-off system and O&M, are quantified. Two other aspects that could have a major impact on the cost of energy are the vertical axis rotor and the jacket. The masses for both are evaluated as proxies for their costs. The former costs are determined to be substantial relative to those of conventional HAWTs. Whereas the latter masses are determined not to be prohibitively greater relative to conventional HAWTs.